All-solid bandgap guiding in tellurite-filled silica photonic crystal fibers - Schmidt, Markus A.; Granzow, Nicolai; Da, Ning; Peng, Mingying; Wondraczek, Lothar; Russell, Philip St. J. (Optics Letters, 2009)
We report all-solid bandgap-guiding fibers formed by pumping molten tellurite glass into silica-air photonic crystal fiber at high pressure. The spectral positions of the guidance bands agree well with multipole simulations and bandgap calculations. The micrometer-diameter tellurite strands are found to contain microheterogeneities (most probably originating from devitrification), which increase the fiber attenuation, although no evidence of crystallization is seen in the bulk tellurite glass. The technique offers a potential route to employing difficult-to-handle glasses, or glasses unsuitable for fiber drawing, in fiber-based amplifiers, modulators, filters, and nonlinear devices.
EAM Import::2019-03-13

Complex Faraday Rotation in Microstructured Magneto-optical Fiber Waveguides - Schmidt, Markus A.; Wondraczek, Lothar; Lee, Ho W.; Granzow, Nicolai; Da, Ning; Russell, Philip St. J. (Advanced Materials, 2011)
Magneto-optical glasses are of considerable current interest, primarily for applications in fiber circuitry, optical isolation, all-optical diodes, optical switching and modulation. While the benchmark materials are still crystalline, glasses offer a variety of unique advantages, such as very high rare-earth and heavy-metal solubility and, in principle, the possibility of being produced in fiber form. In comparison to conventional fiber-drawing processes, pressure-assisted melt-filling of microcapillaries or photonic crystal fibers with magneto-optical glasses offers an alternative route to creating complex waveguide architectures from unusual combinations of glasses. For instance, strongly diamagnetic tellurite or chalcogenide glasses with high refractive index can be combined with silica in an all-solid, microstructured waveguide. This promises the implementation of as-yet-unsuitable but strongly active glass candidates as fiber waveguides, for example in photonic crystal fibers.
EAM Import::2019-03-13

Enhanced photoluminescence from mixed-valence Eu-doped nanocrystalline silicate glass ceramics - Gao, Guojun; Da, Ning; Reibstein, Sindy; Wondraczek, Lothar (Optics Express, 2010)
Intense photoluminescence was observed from mixed-valence Eu-doped nanocrystalline BaAl2Si2O8/LaBO3 glass ceramics. For preparation in air, the ratio between Eu3+ and Eu2+ luminescence depends on synthesis temperature. XRD, TEM and IR absorption spectra were employed to characterize the crystallization process and structural properties of the precursor glass and corresponding glass ceramics. When annealed at 950 °C, the material exhibited photoluminescence more than ten times stronger than was found in its glassy state. Spectroscopic data indicate that during such a heat treatment, even in air, a significant part of the Eu3+ ions is reduced to Eu2+. Lifetime of the 5D0 state of Eu3+ increases with increasing heat treatment temperature. Eu3+ species are largely incorporated on La3+ sites in LaBO3 crystallites whereas Eu2+ locates on Ba2+ sites in the hexacelsian phase. A mechanism for the internal reduction of Eu3+ to Eu2+ is proposed. Spectroscopic properties of the material suggest application in additive luminescent light generation.
EAM Import::2019-03-14

Formation and structure of ionic (Na, Zn) sulfophosphate glasses - Da, Ning; Grassmé, Oliver; Nielsen, Karsten Hansgaard; Peters, Gerhard; Wondraczek, Lothar (Journal of Non-Crystalline Solids, 2011)
Supercooled ortho- and pyrophosphate melts of the type P2O5-EO-A2O (E = Zn2+, Ca2+, Sr2+, Ba2+, Mg2+, Mn2+; A = Li+, Na+, K+) exhibit unusually high sulfate solubility. This enables facile fabrication of low-melting sulfophosphate glasses with SO3 content of up to 25 mol.%. Sulfur is incorporated into those glasses practically exclusively in the form of isolated SO42- groups. The Q-group distribution of phosphate species is dominated by Q1 and Q0 groups, whereby replacing P2O5 with SO3 results in increasing depolymerization. In this way, the glass forming region can readily be extended to compounds with an average number of bridging oxygen per phosphate anion of less than 0.5. In ionic (Na, Zn) sulfophosphate glasses, cations Zn2+ and Na2+ appear to cluster distinctively around PO43- and SO42- groups, respectively.
EAM Import::2019-03-14

High index-contrast all-solid photonic crystal fibers by pressure-assisted melt infiltration of silica matrices - Da, Ning; Wondraczek, Lothar; Schmidt, Markus A.; Granzow, Nicolai; Russell, Philip St. John (Journal of Non-Crystalline Solids, 2010)
All-solid photonic crystal fibers (PCFs) are created by pressure-assisted filling of low-melting-point chalcogenide and tellurite glasses into silica matrix fibers with channel diameters as small as 200 nm. Overcoming to a large extent the problem of viscosity and, thus, process incompatibility of silica and non-silicate optical glasses, the technique provides a unique way of producing waveguiding devices with high core-cladding index-contrast, high optical non-linearity and a transmission range that extends into the mid infrared. In this paper, as a prerequisite for waveguide production, the rheologic properties and controlled flow of highly-viscous liquids under geometrically confined conditions are considered, and deviations from Newtonian behavior are discussed. Because the filling process requires only very small quantities of filling material that do not come into contact with the environment, and because ultra-high cooling rates can be achieved, the technique enables the use of difficult-to-handle or reactive optical glasses.
EAM Import::2019-03-13

Intense red photoluminescence from Mn2+-doped (Na+; Zn2+) sulfophosphate glasses and glass ceramics as LED converters - Da, Ning; Peng, Mingying; Krolikowski, Sebastian; Wondraczek, Lothar (Optics Express, 2010)
We report on intense red fluorescence from Mn2+-doped sulfophosphate glasses and glass ceramics of the type ZnO-Na_2O-SO_3-P_2O5. As a hypothesis, controlled internal crystallization of as-melted glasses is achieved on the basis of thermally-induced bimodal separation of an SO_3-rich phase. Crystal formation is then confined to the relict structure of phase separation. The whole synthesis procedure is performed in air at łeq 800 °C. Electron spin resonance and Raman spectroscopy indicate that Mn2+ species are incorporated on Zn2+ sites with increasingly ionic character for increasing concentration. Correspondingly, in the glasses, increasing MnO content results in decreasing network polymerization. Stable glasses and continuously increasing emission intensity are observed for relatively high dopant concentration of up to 3 mol.%. Recrystallization of the glass results in strongly increasing emission intensity. Dynamic emission spectroscopy reveals only on type of emission centers in the glassy material, whereas three different centers are observed in the glass ceramic. These are attributed to octahedrally coordinated Mn2+ in the residual glass phase and in crystalline phosphate and sulfate lattices, respectively. Relatively low crystal field strength results in almost ideal red emission, peaking around 625 nm. Excitation bands lie in the blue-to-green spectral range and exhibit strong overlap. The optimum excitation range matches the emission properties of GaN- and InGaN-based light emitting devices.
EAM Import::2019-03-13

Photoluminescence of Mn2+ Centers in Chalcohalide Glasses - Yan, Qiqi; Liu, Yinyao; Chen, Guorong; Da, Ning; Wondraczek, Lothar (Journal of the American Ceramic Society, 2011)
We report on photoluminescence from Mn2+-doped chalcohalide glasses of the GeS_2–Ga_2S_3–CsCl system. Upon blue excitation at 447 nm, a broad emission band occurs in the green spectral range from 500 to 600 nm, indicating the presence of tetrahedrally coordinated Mn2+ species. When the Mn2+-concentration is increased up to 2 mol%, an increasingly intense secondary emission band evolves at about 610–660 nm. Meanwhile, the intensity of the green band decreases gradually and shifts toward the red, resulting a very flatten luminescence from 500 to 750 nm, which provides a promising white light emitting source. As for the origin of this unique luminescence behavior of Mn2+, it is proposed that the ligand coordination number of Mn2+ in the present chalcohalide glasses experiences a partial change from tetrahedral to octahedral coordination.
EAM Import::2019-03-12

Viscosity and Softening Behavior of Alkali Zinc Sulfophosphate Glasses - Da, Ning; Krolikowski, Sebastian; Nielsen, Karsten H.; Kaschta, Joachim; Wondraczek, Lothar (Journal of the American Ceramic Society, 2010)
We report on the softening properties and viscosity of glasses from the system ZnO–Na_2O–SO_3–P_2O5 for low-temperature sealing applications. Up to a ratio of network-forming ions PO_43-:SO_42- of about 2:1, a gradual substitution of P_2O5 by SO_3 results in decreasing glass transition and softening temperatures. At the same time, decreasing kinetic fragility is observed, noteworthy even for decreasing the total amount of network former from 44 at.% to 39 at.%. Thermomechanical and calorimetric analyses reveal a distinct SO_42–promoted relaxation phenomenon at temperatures significantly below the macroscopic glass transition temperature, which is interpreted as a result of the formation of an increasingly interconnected assembly of SO_42- and PO_43- units with increasing SO_3 content.
EAM Import::2019-03-12